Social networking services: A digital extension of the surveillance state?. Issue 3 (2nd September 2016) - Jacob Amiradakis, Mark
Abstract : This paper investigates whether or not corporate social networking services (SNS) possess the potential to act as surveillance tools within contemporary society and, as a corollary, operate as coercive and exploitative technologies for the individuals who employ such devices in their daily lives. By relying on an interdisciplinary framework, this investigation argues that exploitative surveillance practices are indeed evident within the digital world of SNS platforms, along with how a performativity pressure (in the form of continuous self-surveillance) has been engendered within the user of such platforms. This has resulted in the creation of coercive digital structures that are then exploited for commercial gain. As such, these SNS technologies can be said to facilitate the expansion of what Foucault terms a disciplinary society, which has then also led to the proliferation of certain "free-floating" forms of control which play a significant part in Deleuze's societies of control . Furthermore, this paper argues for the continuing relevance of both Foucault's insights regarding the panoptic schema, and Deleuze's commentary regarding mechanisms of control, in order to attain a critical understanding of how the practice of online surveillance occurs and from where it is that such an invasive practice derives its impetus.